Soft Skill Management in Improving the Quality and Competence of Human Resources in Islamic Junior High Schools - Abdullah Abdullah; Toyyibatul Mukminatus Sukriyah; Abu Hasan Agus R (Al-Qalam Institute, 2026)
This study aims to examine soft skills management in an effort to improve the quality of education and human resource competency in Islamic schools. The focus of this study includes soft skills management strategies, factors that support and hinder their implementation, and their implications for improving the quality of education. This study uses a qualitative approach with a case study method. Research data were collected from the principal, vice principal of curriculum, teachers, and students through interviews, observations, and documentation studies. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions using content analysis, discourse analysis, and data interpretation. The research findings indicate that soft skills management is implemented through participatory leadership, collaborative learning, the formation of a school culture, and professional development programs. The soft skills developed include communication skills, leadership, teamwork, discipline, and a sense of responsibility. This implementation has an impact on increasing teacher professionalism, the quality of learning, and the formation of student character. This study concludes that soft skills management is an effective strategy for improving the quality of education and human resource competency in a sustainable manner at Islamic junior high school.